Formation, characterization and application of thiol-modified beta-lactoglobulin fibrils complex with chitosan - Chang, Hon Weng (2017)
β-lactoglobulin (β-LG) fibrils have diverse functionalities that make them good emulsifiers and promising foaming agents. However, fabrication of β-LG fibrils under highly acidic conditions (pH 2) has limited their application in food matrixes for food consumption. In addition, β-LG fibrils become unstable when the pH changes and are prone to aggregation. Hence, this study examined the effect of the thiol-modification on β-LG fibrils to improve their functionalities and provide stability against pH changes. Thiol-modified β-LG fibrils were further incorporated into fish oil emulsions by complexing them with chitosan, followed by microencapsulation. In the first stage, the effect of thiol-modification on β-LG fibrils was examined by modifying the carboxyl side groups. The results showed that the highest esterification was obtained at molar ratios of 4:1 (propanethiol:carboxyl groups) under pH 9. Thiolmodification significantly (p < 0.05) enhanced the foaming capacity (550.0 ± 16.7% to 727.8 ± 9.6%), foam stability and emulsifying stability index of the β-LG fibrils. In the second stage, complexation of thiol-modified β-LG fibrils with chitosan was carried out and incorporated into a fish oil emulsion. The results showed that the emulsion droplet size increased with smaller polydispersity indexes upon increasing the chitosan concentrations (0.1% - 0.5%, w/w). The addition of chitosan improved the emulsion stability and decreased the extent of creaming and turbidity loss rate, which improved the oxidative stability of the emulsion significantly (p < 0.05). Moreover, chitosancoated emulsion conferred higher heat stability under thermal treatments (63 °C and 100 °C) as indicated by the consistent droplet sizes. In the third stage, the fish oil emulsion stabilized with thiol-modified β-LG fibrilchitosan complexes was microencapsulated via spray drying using different inlet temperatures (160 °C, 170 °C and 180 °C). The results showed that the fish oil emulsion microencapsulated at 160 °C exhibited significantly higher microencapsulation efficiency (p < 0.05) with enhanced reconstitution properties. Fish oil microcapsules stabilized by thiol-modified β-LG fibril/0.5% chitosan complexes exhibited slightly higher glass transition temperature with a smooth-surfaced as observed via scanning electron microscopy. In the fourth stage, the storage stability and in-vitro digestibility of the microencapsulated fish oil emulsion stabilized with thiolmodified β-LG fibril-chitosan complexes was studied, revealing minimal changes in terms of surface colour and peroxide and p-anisidine values coupled with higher oil retention over 4-weeks of storage period. It was also stable against different ionic strengths. This is related to the thicker wall materials formed by thiol-modified β-LG fibril/0.5% chitosan complexes. It was found that chitosan coating slightly hinder the enzymatic digestion process. The findings of this study suggest that thiol-modification improved the functionalities of β-LG fibrils, including greater tolerance to pH and environmental changes. In addition, the complexation of thiol-modified β-LG fibrils with chitosan contributed to the stability and improved microencapsulation efficiency (> 89%) of a fish oil emulsion.